The Effect of Working Capital Turnover and Receivables Turnover on Return On Investment in PT Gudang Garam Tbk Between 2010 and 2020 - Muhammad Ferdy; Nurismalatri Nurismalatri (Indonesian Financial Review, 2022)
This study aims to determine the Working Capital Turnover (Variable X1) and Accounts Receivable Turnover (Variable X2) on Return on Investment (Variable Y) in PT. Gudang Garam Tbk  from 2010 to 2020. The research method used is descriptive quantitative using secondary data obtained from the Published Financial Report of PT. Gudang Garam, Tbk. from the Indonesia Stock Exchange (IDX) from 2010 to 2020. The method used is multiple regession with fullfiling classical assumption tests. The results show that Working Capital Turnover does not have a significant effect on Return on Investment partially but Receivable Turnover have significant effect on Return on Investment partially. Working Capital Turnover and Receivable Turnover have a significant effect on Return on Investment simultaneously.